Umaga sa Katayan at Iba Pang Tula - Atilano, Ronald Araña (Likhaan: The Journal of Contemporary Philippine Literature; Vol 16 No 01 (2022): LIKHAAN 16: The Journal of Contemporary Philippine Literature, 2023)
The author deployed these poems to do a reconnaisance of the city of memory, wander around its old streets and old citadels, and go back to the house his father still inhabits.